Trade in African Grey Parrots for Belief-Based Use: Insights From West Africa's Largest Traditional Medicine Market - Assou, Délagnon; Elwin, Angie; Norrey, John; Coulthard, Emma; Megson, David; Ronfot, Delphine; Auliya, Mark; Segniagbeto, Gabriel H.; Martin, Rowan O.; D'Cruze, Neil (Frontiers in Ecology and Evolution, 2021)
Over 1.2 million wild-sourced African Grey parrots (Psittacus erithacus) have reportedly been traded internationally since the 1970s, the majority of which were taken from the wild with serious implications for conservation, animal welfare and biosecurity. While international trade has mostly been for the pet trade, in some West African countries, Grey parrots are also consumed for belief-based use. However, to date there has been little research into the scale and scope of this trade and its drivers. Here, we explore multiple facets of the trade in Grey parrots for belief-based use through interviews with five vendors at the largest ‘fetish’ market of West Africa in Togo. We focus on understanding the purpose of medicinal and spiritual use of Grey parrots, and the socio-economic dimensions of this trade. Parrot heads were the most valuable and most frequently traded body part over the last year (2017), sold primarily for the medicinal purpose of helping to “improve memory”. Feathers were the most common transaction for spiritual use, largely purchased for “attracting clients”, “love”, and to “help with divorce”. Whole parrots and parrot heads had also been traded for spiritual use, mainly for “good luck” and “protection from witchcraft”. Our findings suggest approximately 900 Grey parrots were traded over the past 10 years in the market. Most vendors perceived an increase in the rarity of Grey parrot body parts over the past 5 years, which may reflect increased restrictions on international trade and/or the deteriorating state of wild populations. Although the sale of feathers collected from beneath roosting sites does not negatively impact wild populations, the relatively low value of these parts compared with other parrot derivatives and live parrots, suggests there may be minimal opportunity to leverage market mechanisms to protect wild populations through sustainable use. We identify a need for further investigations to examine the complex relationship between capture to supply the international pet market, a process in which many parrots die, and the local trade in belief-based use of derivatives.